2019
DOI: 10.1007/s10584-019-02552-0
|View full text |Cite
|
Sign up to set email alerts
|

Emotional foundations of the public climate change divide

Abstract: The worldwide rise of climate skeptical political leaders endangers sorely needed political efforts to mitigate climate change. In addition, climate skepticism expressed by the political elites may spread to the electorate, thus ultimately affecting mitigation actions at the population level. It is crucial to better understand the psychological mechanisms underlying elite influences on public opinion formation and polarization. Here we show how affective processes contribute to these top-down influences using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…We cannot be sure if there is some lingering unaccounted-for artifact that may drive the observed relations between support for Trump and time on origin and impact climate beliefs. However, our results parallel those of Hahnel et al (2019) who found similar effects using within-participants pre-and post-election data, giving more confidence to the conclusions we can draw from our findings. It is important to triangulate findings across multiple methods, as together, the conclusions drawn from multiple independent studies are more robust than conclusions that can be drawn from a single study.…”
Section: Limitations and Future Directionssupporting
confidence: 90%
See 2 more Smart Citations
“…We cannot be sure if there is some lingering unaccounted-for artifact that may drive the observed relations between support for Trump and time on origin and impact climate beliefs. However, our results parallel those of Hahnel et al (2019) who found similar effects using within-participants pre-and post-election data, giving more confidence to the conclusions we can draw from our findings. It is important to triangulate findings across multiple methods, as together, the conclusions drawn from multiple independent studies are more robust than conclusions that can be drawn from a single study.…”
Section: Limitations and Future Directionssupporting
confidence: 90%
“…Our results and those from similar studies (i.e., Hahnel et al 2019) are theoretically and practically important, and more research is needed to improve our causal understanding of the following: to what extent and why supporters' climate-related beliefs align with political leaders' opinions; why that alignment may change when the leader rises to power; and how these changes in climate beliefs ultimately affect climate actions and policy support. Additionally, as climate change becomes an increasingly urgent and more frequently debated political topic, it is important to examine how the rise of climate-friendly political leaders influences public engagement with climate change and whether that influence occurs through a similar process observed here.…”
Section: Limitations and Future Directionssupporting
confidence: 50%
See 1 more Smart Citation
“…President Trump has repeatedly expressed his skepticism of climate change on social media (Matthews, 2017). Following his election in 2016, belief in climate change actually decreased in the United States, for both Republicans and Democrats, suggesting that people update their beliefs based on cues from political leaders (Hahnel et al., 2020; see also Zawadzki et al., 2020). Interestingly, the changes in climate change belief from pre‐ to postelection were mediated by increased positive feelings toward the Republican party (by both Republicans and Democrats), and those with the most pronounced increases were the ones who most strongly reduced their climate change beliefs.…”
Section: Psychological Risk Factorsmentioning
confidence: 99%
“…In some countries, major political parties and politicians deny the science of climate change. For example, in the US, the Republican party and President Trump routinely cast doubt on the existence and seriousness of climate change (Hahnel et al, 2020;Porter et al, 2019). Politicians holding power who deny climate change, will -as a matter of course -do what they can to slow or halt political action on climate change.…”
Section: Beliefmentioning
confidence: 99%